Wnt pathway component LEF1 mediates tumor cell invasion and is expressed in human and murine breast cancers lacking ErbB2 (her-2/neu) overexpression - Anthony Nguyen (2018)
This study examines the role of LEF1, a component of the Wnt signaling pathway, in human breast and murine mammary carcinoma and its relationship to ErbB2 (her-2/neu) expression. Mammary tissue and tumors from 5 different Wnt pathway-activated transgenic mouse strains and 5 different ErbB2 pathway-activated transgenic mouse strains were studied for the amount and distribution of expression of 6-catenin and LEF1. Fourteen samples of human infiltrating ductal breast cancer arising from a background of ductal carcinoma in situ (DCIS) were analyzed for LEF1, estrogen and progesterone receptor (ER and PR) and her-2/neu expression. In vitro, the effect of estradiol on LEF1 protein expression was examined in several breast cancer cell lines. The functional role of LEF1 was analyzed by a Matrigel invasion assay following transfection of breast cancer cell lines with either an LEF1 expression construct or a dominant-negative LEF1 construct. A significant (p=0.023) negative correlation between the expression of LEF1 and her-2/neu was observed in human breast cancer. LEF1 was strongly expressed, and β-catenin had nuclear localization, in mammary tumors derived from Wnt pathway transgenic mice but not in ErbB2 pathway transgenic mice. In estrogen-receptor-positive breast cancer cell lines, LEF1 protein expression increased significantly following estradiol incubation (>200% of baseline). Following transient transfection, overexpression of LEF1 promoted and dominant-negative LEF1 inhibited tumor cell invasion. LEF1, a downstream component of the Wnt signaling pathway, defines a distinct, her-2/neu negative (non-overexpressing) subset of breast/mammary cancers in both humans and mice, mediates breast cancer cell invasion, and may be regulated in part by estradiol.